2017
DOI: 10.1093/aob/mcx122
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of neutral and non-neutral processes to clinal variation in calyx lobe length in the series Sakawanum (Asarum: Aristolochiaceae)

Abstract: Divergent selection may have driven the calyx lobe length variation in series Sakawanum taxa, although the underlying mechanism is still not clear. The low genetic differentiation indicates recent divergence and/or gene flows between geographically close taxa. These neutral processes would also affect the clinal variation in calyx lobe lengths. Overall, this study implies the roles of population history and divergent selection in shaping the current cline of a flower trait in the series Sakawanum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Previous studies showed relatively low genetic differentiation between the two species (F ST = 0.087 in EST-SSR data; Takahashi et al 2019) and Q CT -F CT comparative analysis, which test whether selection is involved in the evolution of quantitative traits (Whitlock 2008). This suggests that divergent selection may have affected calyx lobe length differentiation (Takahashi et al 2018). Flowers with elongated filiform appendages or bracts are considered to be associated with visual attraction of pollinators by increasing the display size and acting as landing platforms (Policha et al 2016;Katsuhara et al 2017).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies showed relatively low genetic differentiation between the two species (F ST = 0.087 in EST-SSR data; Takahashi et al 2019) and Q CT -F CT comparative analysis, which test whether selection is involved in the evolution of quantitative traits (Whitlock 2008). This suggests that divergent selection may have affected calyx lobe length differentiation (Takahashi et al 2018). Flowers with elongated filiform appendages or bracts are considered to be associated with visual attraction of pollinators by increasing the display size and acting as landing platforms (Policha et al 2016;Katsuhara et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…1a) distributed in warm-temperate evergreen forests of the Japanese Archipelago. Although these two species are closely related (Takahashi et al 2019), they show a considerable differences in calyx lobe lengths: A. costatum has a short calyx lobe (10-20 mm), which is considered to be ancestral, whereas A. minamitanianum has a remarkably elongated calyx lobe (70-180 mm) (Takahashi et al 2018). Previous studies showed relatively low genetic differentiation between the two species (F ST = 0.087 in EST-SSR data; Takahashi et al 2019) and Q CT -F CT comparative analysis, which test whether selection is involved in the evolution of quantitative traits (Whitlock 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-measurable traits are less affected by natural environment, social and economic conditions, and are mainly controlled by genetics. The frequency of variation has different distribution in various human groups or regions in the world, so non-measurable traits always play a leading role in anthropological research [10,11].…”
Section: Haiou Zhang Et Al: Contrastive Characteristic Analysis Of Ma...mentioning
confidence: 99%